The antimicrobial peptide HBD-2 and the Toll-like receptors-2 and -4 are induced in synovial membranes in case of septic arthritis - Varoga, D.; Klostermeier, E.; Paulsen, F.; Wruck, C.; Lippross, S.; Brandenburg, L. O.; Tohidnezhad, M.; Seekamp, A.; Tillmann, B.; Pufe, T. (Virchows Archiv : an international journal of pathology, 2009)
Septic arthritis is frequently observed especially in immune-compromised or chronically diseased patients and leads to functional impairment due to tissue destruction. Recently, production of antimicrobial peptides (AMP) was observed in articular cartilage after exposure to bacteria. This report examines the role of synoviocyte-derived AMPs in innate defense mechanisms of articular joints. Samples of healthy, low-grade synovialitis and septic synovial membranes were assessed for the expression of human β-defensin-2 (HBD-2) and Toll-like receptor-2 and -4 (TLR) by immunohistochemistry and enzyme-linked immunosorbent assay (ELISA). A stable synoviocyte line (K4IM) was used for in vitro experiments and assayed for endogenous HBD-2 and TLR production after exposure to inflammatory cytokines or bacterial supernatants by reverse transcription polymerase chain reaction (RT-PCR), real-time RT-PCR, Western blot, ELISA, and dual luciferase assay. Healthy human synovial membranes and cultured synoviocytes are able to produce HBD-2 and TLR-1–5 at basal expression levels. Samples of bacteria-colonized synovial membranes produce higher levels of HBD-2 when compared with samples of healthy tissues. K4IM synoviocytes exposed to Staphylococcus aureus , Pseudomonas aeruginosa , or proinflammatory cytokines demonstrated a clear HBD-2 transcription and protein induction. TLR-2 and -4 are known to have a critical role in the recognition of gram-positive and gram-negative bacteria in epithelia and are induced in mesenchymal synoviocytes after bacterial exposure on transcription and on protein level. This report demonstrates an unappreciated role of synovial membranes: samples of septic synovial membranes and cultured synoviocytes exposed to bacteria produce increased amounts of the AMP HBD-2 and the bacteria recognition receptors TLR-2 and -4. The induction of anti-inflammatory pathways in infected synoviocytes suggests involvement in intra-articular defense mechanisms.